Benign thyroid disease and the risk of breast cancer: An updated systematic review and meta-analysis - Han, Mingyue; Wang, Yao; Jin, Yuanhui; Zhao, Xue; Cui, Haiying; Wang, Guixia; Gang, Xiaokun (Frontiers in Endocrinology, 2022)
Background The correlation between benign thyroid disease (BTD) and breast cancer (BC) has long been discussed. However, the definite relationship and potential mechanism between them are still disputed. The current meta-analysis aimed at performing a comprehensive assessment of the relationship between different types of benign thyroid disease and the risk of breast cancer, furthermore, assessing whether benign thyroid disease exerts an influence on the aggressiveness of breast cancer. Method A systematic literature search (PubMed, Web of Science, MEDLINE, and Embase databases) identified studies to evaluate the correlation between BTD and BC risk. Data were analyzed using version 16.0 STATA software, including the odds ratio (OR) and its corresponding 95% confidence intervals (CIs). Publication bias and quality assessment were conducted for the included studies. Result Overall, 18 studies involving 422,384 patients with BTD were incorporated. The outcome showed that autoimmune thyroiditis (OR: 2.56, 95%CI: 1.95–3.37, I2=0.0%, p=0.460), goiter (OR: 2.13, 95%CI: 1.19-3.79, I2=80.6%, p=0.000), and Graves’ disease (OR: 5.01, 95%CI: 1.49-16.82, I2=0.0%, p=0.358) was connected with a higher risk of BC. Both hypothyroidism (OR: 0.82, 95%CI: 0.64-1.04, I2=85.0%, p=0.000) and hyperthyroidism (OR: 1.07, 95%CI: 0.93-1.24, I2=24.9%, p=0.000) had no significant association with the risk of BC. Additionally, the pooled analysis showed no apparent correlation between BTD and aggressiveness of BC. However, subgroup analysis indicated a positive relationship between BTD and aggressiveness of BC in the Europe subgroup (HR: 2.05, 95%CI: 1.32-3.17, I2=86.4%, p=0.000). Conclusion Autoimmune thyroiditis, goiter, and Graves’ disease are connected with an increased risk of BC. Furthermore, subgroup analysis suggested that BTD increases the aggressiveness of BC in the European population geographically. Nevertheless, further research is needed to prove these discoveries.